Sympathetic Neurotransmitters and Tumor Angiogenesis—Link between Stress and Cancer Progression. (26th April 2010) - Tilan, Jason; Kitlinska, Joanna
Abstract : Recent evidence supports a longstanding hypothesis that chronic stress can influence tumor growth and progression. It has been shown that sympathetic neurotransmitters, such as catecholamines and neuropeptides, can affect both cancer cell growth and tumor vascularization. Depending on neurotransmitter and type of tumor, these effects can be both stimulatory and inhibitory. Norepinephrine (NE) and epinephrine (E) are potent stimulators of vascularization, acting both by inducing the release of angiogenic factors from tumor cells and directly on endothelial cell (EC) functions. As a result, activation of the adrenergic system increases growth of various types of tumors and has been shown to mediate stress-induced augmentation of tumor progression. Dopamine (DA), on the other hand, interferes with VEGF signaling in endothelial cells, blocks its angiogenic functions and inhibits tumor growth. Another sympathetic neurotransmitter coreleased with NE, neuropeptide Y (NPY), directly stimulates angiogenesis. However, proangiogenic actions of NPY can be altered by its direct effect on tumor cell proliferation and survival. In consequence, NPY can either stimulate or inhibit tumor growth, depending on tumor type. Hence, sympathetic neurotransmitters are powerful modulators of tumor growth and can become new targets in cancer therapy.